IMPLEMENTASI UNDANG-UNDANG NOMOR 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK DI KANTOR KEPOLISIAN RESORT KLATEN - Hertina, Meisayu Lisa (JI@P, 2015)
This research aimed to provide an overview of the implementation of law no.14 of 2008 concerning the openness of public information at Resort PoliceOffice in Klaten Regency. This research also aimed to find out supporting aswell as inhibating factors that are considered to affects the implementationand the strategies to implement the defined policies. It is also expected thatbased on research result, recomendation can be formulated concerning theimplementation related to some policies implementation of Law no.14 theyear of 2008. This research exercised Van Meter Van Horn theory dealingwith the various factors affecting policy performance. However, this researchwas aimed to emphasize on studying the process of policy implementation.Case study method was employed for describing in detail and in depth thefacts happened in the research site. Purposive sampling technique wasimplemented. Interactive analysis model as suggested by Miles andHuberman was employed in this study. To validate the research finding, datatriangulation was applied. Research results shows that Resort Police Officein Klaten Regency has already implemented openness policy concerningpublic information accords to the technical operation instructions. Someimprovements related to the implementation of the policy, however, are stillneeded. The needed improvement that are suggested among others are therecruetment of the employee working in Public Relation Section, moresupporting facilities, improving facilities, increasing communication andcoordination unit.Keywords: implementation, openness, public information